THE ROLE OF INFORMATION SYSTEMS IN THE FINANCIAL INDUSTRY (BCA MOBILE) - Dewi Puspaningtyas Faeni; Nazwa Dea Devilia (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
In this era of globalization, rapid advances in technology and information, especially on the internet, are quite fast. With the internet, everything is always fast and easy. Advances in internet technology have changed many aspects of human life significantly. This is because the internet has now become a very important need for many people, especially those who live in rural areas. This is supported by statistical data from a January 2019 report from Hootsuite, a social media platform from Canada, and We are Social, a social media company from England. Based on research findings from Hootsuite and We Are Social reports, the number of Indonesian internet users increased to 150 million in 2019, which is around 13 percent of the 17 million users in 2018. We are social & Hootsuite, 2019). Nowadays, internet use is not only limited to social media and communication media; it can also be used to play online games, make travel reservations, buy goods, run a business, and carry out financial transactions. In this era of globalization, people carry out various banking transactions. They more often use banking services offered by several banks in Indonesia. The most common term the general public uses to describe this type of bank transaction is “Electronic Banking”. (Online banking). E-banking is a banking service that uses electronic media as a medium so that savings are no longer lost by customers or thieves. (Sari, 2013). There are many types of electronic banking available in Indonesia, including SMS, telephone, mobile, and online banking. In Indonesia, mobile banking, or e-banking, is becoming increasingly popular. Mobile banking is a banking practice that uses internet technology as a medium for carrying out transactions using smartphones. You can use mobile banking services by using the menu that is available in the application. Mobile banking offers convenience to small businesses as it can handle bank inquiries in an easy way. In addition, it allows transactions to occur whenever and wherever is most convenient. However, there is still an Indonesian population that still prefers manual transactions using paper (cash) currency because most Indonesian sellers only offer manual transactions rather than the internet. There are many applications mobile banking available in Indonesia, including BCA Mobile, Mandiri Online, BRI Mobile, BNI Mobile Banking, Mega Mobile, HSBC Mobile banking, D-Bank, and others. As mentioned above, the mobile banking application can only be accessed via the iOS and Android smartphone application which can be installed via Playstore or App Store. (Faeni et al, 2023)